HUBUNGAN SOSIAL BUDAYA, PERAN ORANG TUA, DAN KUALITAS MAKANAN DENGAN PERILAKU PEMBERIAN MP-ASI DINI PADA BAYI USIA 0-6 BULAN DI PMB “A” - Valerie, Diva; Anggraeni, Milka; Ayu, Rita (SENTRI: Jurnal Riset Ilmiah, 2023)
Introduction: Giving MP-ASI that is too early or inappropriate can cause health problems in children. In fact, the practice of giving MP ASI early in Indonesia is still widely practiced. Early MP ASI can have an impact on high incidence of infections such as allergies, diarrhea, respiratory infections to growth disorders Purpose: The purpose of this study was to determine the socio-cultural relationship, the role of parents, and the quality of food by giving early MP ASI to infants aged 0-6 months at PMB "A". Methods: This research method uses a descriptive analytic research method with a cross sectional approach. The population in this study were mothers with children aged 0-6 months who visited PMB "A" from September to November 2022, namely 119 mothers. The sampling technique in this study used a simple random sampling technique and obtained a total sample of 55 respondents. Data analysis techniques using univariate analysis and bivariate analysis. Results: There is a relationship between socio-culture, parental roles, and food quality with the behavior of early complementary feeding in infants aged 0-6 months at PMB Aditia Sembiring. Conclusion : It was concluded that out of 54 mothers, there were 34 mothers who did not give early mpation to their babies, 27 stated that there was a culture of giving mpation in their social environment, 29 mothers stated that there was a role from parents, and 44 mothers gave early complementary breastfeeding with food which is of good quality. There is a relationship between socio-culture and the behavior of early complementary breastfeeding with a p-value of 0.002. There is a relationship between the role of parents and the behavior of early complementary breastfeeding in with a p value of 0.016. There is a relationship between food quality and the behavior of early complementary breastfeeding with a p value of 0.000.